The role of speed, change of direction, and momentum by position and starting status in Division I collegiate football players - Mann, J. B.; Cowley, N.; Weakley, J. (The Journal of Strength and Conditioning Research, 2025)
This study (a) investigated differences between big, mid, and skill positions in sprint and change of direction times and momentum; (b) compared starting and nonstarting athletes; and (c) investigated whether thresholds can be developed to distinguish between starting and nonstarting Division 1 collegiate football athletes. Data from 496 collegiate football players who completed the 40-yard dash, pro-agility, and L drill were analyzed. Momentum was calculated using body mass and the average velocity during each test. To assess differences between positions and starters and nonstarters, data were analyzed using linear mixed models with effect size ±95% confidence intervals. Receiver operating characteristic (ROC) curves were generated to determine whether a cutoff value could be used to distinguish starters from nonstarters. Significant differences for both time and momentum were found between positional groups and starters and nonstarters for all tests in all positions. Starting skill position players tended to have greater differences in sprint or change of direction times and starting big players had greater sprint momentum. However, it should be noted that all ROC curves demonstrated relatively poor predictive value. Collectively, these findings demonstrate that bigger, faster players are preferentially selected in collegiate Division 1 football and there may be value in coaches collecting and assessing different outcome measures (e.g., sprint times and sprint momentum) depending on the positional group of the player. Finally, it should be acknowledged that setting binary thresholds to guide selection decisions is ill-advised and that speed, change of direction, and momentum are only one piece of the performance puzzle.